Effects of Dengue 2 Virus inoculation on Toxorhynchites splendens larvae - Shafee, N.; AbuBakar, Sazaly (2006)
Potential occurrence of dengue 2 virus (DENV-2)-induced apoptosis in mosquito larvae was investigated. Heads of Toxohrynchites splendens mosquito larvae were inoculated with DENV-2 inoculum at multiplicity of infection of 0.0005-0.001 plaque forming unit per cell. After 7 days of incubation, the larvae heads were severed and squashed onto slides. Following immunofluorescence staining with mouse polyclonal antibody against DENV-2, antigens were detected in 17.5 of the total cells counted. Counterstaining of the cells using colorimetric apoptotic staining method revealed that 21.7 of the antigen-positive cells were in apoptotic state. Statistical analyses of the data showed that the induction of apoptosis was directly correlated to the DENV-2 infection and not merely a metamorphic programmed cell death response.